Effect of relative humidity on O3 and NO2 oxidation of SO2 on α-Al2O3 particles. (October 2017) - Liu, Wenjun; He, Xiang; Pang, Shufeng; Zhang, Yunhong
Abstract: Heterogeneous reactions of SO2 /O3 and SO2 /NO2 with α-Al2 O3 particles at different RHs were investigated using a gas-flow system combined with microscopic Fourier transform infrared (micro-FTIR) spectrometer. The results show that the trace gas O3 or NO2 leads to rapid conversion of SO2 to sulfate on the surface of α-Al2 O3 particles in initial stage and then conversion rate decreases in the following stages. The rate of sulfate formation and uptake coefficient (γ) for SO2 in the two systems as a function of relative humidity (RH) are determined for the first time, which are all strongly enhanced more than seven-fold as the RH increase from 15% to 95% in initial stage for SO2 /O3 and SO2 /NO2 . Moreover, the γ in the system of SO2 /O3 on α-Al2 O3 particles is more than 3-fold than that of SO2 /NO2 for the similar RH condition. Our results may be broadly applicable to understand the effects of RH and trace gases (e.g., O3, NO2 ) for the converting SO2 into sulfate on the mineral dust, which supply basic data for atmospheric chemistry modeling studies. Graphical abstract: Highlights: O3 or NO2 leads to rapid conversion of SO2 to sulfate on α-Al2 O3 particles. Compared to NO2, O3 is easier to oxidize SO2 to sulfate. Reactions of SO2 /O3, SO2 /NO2 on α-Al2 O3 particles exhibit RH dependence. The reaction rates and uptake coefficients increase with increasing RH.